Association between Cognitive Decline in Older Adults and Use of Primary Care Physician Services in Pennsylvania - Nicole R. Fowler; Lisa A. Morrow; Li-Chuan Tu; Douglas P. Landsittel; Beth E. Snitz; Eric G. Rodriquez; Judith A. Saxton (SAGE Publishing, 2012)
Objective : To assess the relationship between cognitive decline of older patients (≥ 65 y) and use of primary care physician (PCP) services over 24 months. Design : Retrospective analysis of prospectively collected data from a cluster randomized trial that took place from 2006-2010 and investigated the relationship between formal neuropsychological evaluation and patient outcomes in primary care. Setting : Twenty-four PCPs in 11 practices in southwestern Pennsylvania. Most practices were suburban and included more than 5 PCPs. Participants : A sample of 423 primary care patients 65 years old or older. Measurements : The association between the number of PCP visits and a decline in cognitive status, as determined by multivariable analyses that controlled for patient-level, physician-level, and practice-level factors (eg, patient age, comorbidities, and symptoms of depression; practice location and size; PCP age and sex) and used a linear mixed model with a random intercept to adjust for clustering. Results : Over a 2-year follow-up, 199 patients (47.0%) experienced a decline in cognitive status. Patients with a cognitive decline had a mean of 0.69 more PCP visits than did patients without a cognitive decline ( P < .05). Conclusions : Early signs of cognitive decline may be an indicator of greater use of primary care. Given the demographic trends, more PCPs are likely to be needed to meet the increasing needs of the older population.